Do Audit Firms’ Financial Statements Provide Information about Audit Quality? - He, Shaohua; Lisic, Ling Lei; Tan, Liang; Wang, K. Philip (The Accounting Review, 2025)
ABSTRACT Whether audit firms should disclose financial statements is controversial among investors, practitioners, and regulators. The debate centers on whether audit firms’ financial statements provide information about audit quality. Using hand-collected data from U.K. audit firms’ financial statements, we construct four measures that capture audit firms’ resource investments (i.e., human capital, workplace environment, technologies) and risk exposures (i.e., litigation provisions). We find that increases in audit firms’ staff costs, investments in tangible assets and IT software, and reductions in litigation provisions are associated with improved audit quality. The information in audit firms’ financial statements is not contained in their transparency reports or regulatory inspection reports. Additional tests show that increases in audit firms’ staff costs and tangible assets, as well as reductions in litigation provisions, are associated with improved audit efficiency. JEL Classifications: M40; M42.